Communication Architecture for Biodiversity Information Retrieval(CABIR) - K.S, Sarinder K.; Lim, L.H.S; K., Dimyati; A.F., Merican (Malaysian Journal of Science, 2009)
This paper focused on biodiversity database integration. Firstly, the problems are studied and explained. They are divided into four broad categories, which are technical, political, syntactical and semantical. Following this, the approaches to build a database integration system were reviewed after which, the mediator based approach was selected. A new database integration system, which is called CABIR (Communication Architecture for Biodiversity Information Retrieval) was built and discussed thoroughly in this paper. A performance test was also conducted to measure the efficiency of the CABIR system. The development of CABIR system is expected to contribute in the field of biodiversity as this system could link distributed biodiversity databases regardless of the heterogeneity and the platform they were built upon. Artikel ini memberi tumpuan kepada integrasi pangkalan data biodiversiti. Pertama sekali, masalah-masalah yang dihadapi dikenalpasti and dijelaskan. Masalah-masalah ini dibahagikan kepada empat kategori iaitu teknikal, politikal, sintetikal and semantikal. Seterusnya, langkah-langkah untuk membangunkan satu integrasi pangkalan data dikaji setelah â€œmediatorâ€ telah dipilih. Satu sistem integrasi pangkal an data yang baru, iaitu CABIR (Communication Architecture for Biodiversit y Information Retrieval) telah dibangunakan and dibincang dengan teliti dalam artikel ini. Satu ujian prestasi telah dijalankan untuk menentukan kecekapan sistem CABIR. Pembangunan sistem CABIR ini dijangka akan menyumbang kepada bidang biodiversiti kerana sistem ini boleh menghubungkan pangkalan data biodiversiti yang bertaburan tanpa mengira kepelbagaian and platform dimana pangkalan- pangkalan data tersebut dibina.